2018
DOI: 10.4012/dmj.2017-125
|View full text |Cite
|
Sign up to set email alerts
|

Influence of grade and surface topography of commercially pure titanium on fatigue properties

Abstract: The objective was to investigate the influence of grade and surface topography of commercially pure titanium (Cp-Ti) on fatigue properties evaluated via staircase method. Cp-Ti grades 2 and 4 were roughened by shot blasting and acid etching, and compared with machined specimens. Yield force under static loading for Cp-Ti grades 2 and 4 were 672±51 and 1,088±93 N for machined and 724±99 and 1,118±96 N for roughened group. Yield force under cyclic loading for Cp-Ti grades 2 and 4 decreased 27 and 40% compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Shear fatigue strengths were calculated using a staircase method based on gathered mean load‐to‐failure (stress level) data under different cyclic fatigue conditions. Fatigue strength is not a straightforward property to measure, and many testing procedures have been devised to determine the yield force for cyclic loading, including using the S‐N curve (stress vs. number of cycles), constant stress level testing, response or survival method (also known as the probit method), step‐test method, plot method, and extreme value method . All these methods require extensive time, effort, and application of repeated loads to a large number of samples.…”
Section: Discussionmentioning
confidence: 99%
“…Shear fatigue strengths were calculated using a staircase method based on gathered mean load‐to‐failure (stress level) data under different cyclic fatigue conditions. Fatigue strength is not a straightforward property to measure, and many testing procedures have been devised to determine the yield force for cyclic loading, including using the S‐N curve (stress vs. number of cycles), constant stress level testing, response or survival method (also known as the probit method), step‐test method, plot method, and extreme value method . All these methods require extensive time, effort, and application of repeated loads to a large number of samples.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclic fatigue load was evaluated after 1×10 6 cycles at a frequency of 10 Hz. A loading frequency of 10 Hz was used because previous experiments showed no apparent differences in fatigue in cyclic fracture loads of 2 Hz 15) and 10 Hz 25) . Furthermore, other studies suggested that loading be limited to 1×10 6 cycles during fatigue tests for standardization purposes 34,35) .…”
Section: Discussionmentioning
confidence: 99%
“…3). Loading conditions were established according to past research 15,25) . Cyclic fatigue load was evaluated after 1×10 6 loads at a frequency of 10 Hz in 37°C distilled water using the staircase method 14) .…”
Section: B-2)mentioning
confidence: 99%
“…Although base metal alloys have superior mechanical properties, their poor biocompatibility, low corrosion resistance, and allergenic properties have increased the interest in titanium in prosthetic treatments [ 4 , 5 ]. Titanium is a suitable material for dental restorations because of its excellent biocompatibility, high physical and mechanical properties, low density, and superior corrosion resistance [ [6] , [7] , [8] ]. Due to these advantages, titanium has become a suitable material option for patients who have metal allergies, especially [ 9 ].…”
Section: Introductionmentioning
confidence: 99%